SURVIVAL STRATEGIES OF PAJAK IKAN LAMA AS ONLINE MARKETS RISE - Nanta, Bayu Mega; Cahyani, Erika Setia; Sanda, Juana Tria; Rahadatul 'Aisyi, Luthfiyyah (Academic Solution Publisher, 2024)
This research focuses on the survival strategies applied by traders in Pasar Ikan Lama, Medan, who have been operating traditionally for at least five years. Pasar Ikan Lama is a well-known textile market in Medan City, which attracts not only local people but also visitors from other regions such as Aceh, Padang, and Riau. In the face of challenges from the proliferation of online shopping, traders in the Pasar Ikan Lama must adapt to the rapid changes in information and communication technology. This study identifies various strategies used by traders to attract buyers, such as providing discounts and utilizing online sales. Data analysis was conducted through interviews and note collection to understand more about the strategies implemented by merchants. The research also highlights the importance of understanding existing digital tools, where digital optimization can provide a more personalized experience for customers. However, the challenge faced is the need to learn and invest in new technologies. Overall, this research provides insights into how traditional market traders can remain relevant and competitive in the digital age, as well as the importance of integrating digital strategies in their businesses to achieve long-term success.